Client/server architecture having a dynamic and transparent middle tier - Mohd Ali, Borhanuddin; Choong, Khong Neng; Prakash, Veeraraghavan (2010)
There is disclosed a client / server digital computing network architecture that works in a three-tier environment and having a dynamic middle-tier configuration. In the three-tier architecture of the present invention, a middle tier is added between the user (client) and the central server. The middle-tier is adapted to be dynamic for flexibility to handle a large number of users and to address the issues of bandwidth utilization and network congestion in an efficient, effective and transparent manner. In the present invention, a client workstation is selected to be dynamic proxy where a Dynamic Application Proxy Server (DAPS) within the client workstation is adapted to handle and serve request from subsequent remote clients on behalf of the central server, and provides the only connection to a Server Application in a central server. This invention effectively delegates all client request to the DAPS while freeing the central server to conduct other more specific operation.